Pemerolehan Bahasa pada Anak 4-5 Tahun dengan Terapi E-Book - ., admin; ., Yuspendi (Zenit, 2015)
Creative and innovative treatment of media can increase childrens interest in learning the language acquisition. The purpose of this paper is to reveal an increase in language skills in children with E-book “Asal-usul Padi”treatment. This paper uses the method of instructional media development and action research (action research). Media were developed with media programming by displaying various forms of impressions in the E-book “Asal-usul Padi”tools both visually and audiovisually. This treatment of media is applied to sensorimotor as a neurological processes by manipulating, facilitating,and adapting the environment in order to achieve improvement, repair, and maintenance competence language in children. The result of this research showed that the increasing the proficiency index is registered with hi - tech media treatment and able boost both value and creative character in children, especially the age of 5 years. It was seen in the change of any action bythe author based on the content and speech acts as well as the measurement index of child language skill, especially in terms of syntactic and pragmatic development. In addition, the development of media for language acquisition will foster motivation, creativity, and positive character traits inchildren. Thus, development of media treatment of language acquisition can be used as a model for the improvement of language skills in normal children.Keywords: language acquisitionin children, the development of syntactic, pragmatic development, treatment E-book “Asal-usul Padi”